THE TONOPLAST TRANSPORT SYSTEMS OF PLANT VACUOLES AND THEIR POTENTIAL APPLICATION IN BIOTECHNOLOGY - S. V. Isayenkov (Biotechnologia Acta, 2013)
The pivotal role of plant vacuoles in plant survival was discussed in the review. Particularly, the providing of cellular turgor, accumulation of inorganic osmolytes and nutrients are the primary tasks of these cellular organelles. The main mechanisms of tonoplast transport systems were described. The known transport pathways of minerals, heavy metals, vitamins and other organic compounds were classified and outlined. The main systems of membrane vacuolar transport were reviewed. The outline of the physiological functions and features of vacuolar membrane transport proteins were performed.